Synthesis and antitumour evaluation of benzopsoralen analogues - Oliveira, Ana M. A. G. (2007)
The synthesis of five new analogues of benzopsoralens, derived from xanthen-9-one and carbazole is described. The preparation of the hydroxylated precursors, their formylation and the formation of the pyranone ring, by the reaction between ortho-formylated heterocycles and diethyl malonate in EtOH, will be discussed. The inhibitory effect on the growth of human tumour cell lines (MCF-7, SF-268 and NCI-460) of the final products was evaluated and is discussed in terms of the 3D-geometry and electronic density distribution. The compounds showing significant biological activity in this study were those having angular structures.